2018
DOI: 10.1002/jsfa.9008
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of diethylacetal and acetaldehyde during beer fermentation and storage process

Abstract: The newly established method can be used to assess acetaldehyde level and flavor quality in beer more scientifically. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 48 publications
4
18
0
Order By: Relevance
“…It has been shown that ADH1 encodes a protein that performs as the major catalyst of acetaldehyde reaction, by contrast with ADH2, which predominantly encodes a protein for ethanol intake and ethanol transfer to acetaldehyde. It was also demonstrated that, although there is no distinction in cell growth and concentrations of other volatile compounds during fermentation between the mutant and the pattern brewing yeast strains, the final acetaldehyde content from the mutant strain decreased to approximately one-third that of the pattern strain, which is an important advance to avoid or reduce acetaldehyde off-flavors in beer [7,11,53,73,75].…”
Section: Complementary Beer Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ADH1 encodes a protein that performs as the major catalyst of acetaldehyde reaction, by contrast with ADH2, which predominantly encodes a protein for ethanol intake and ethanol transfer to acetaldehyde. It was also demonstrated that, although there is no distinction in cell growth and concentrations of other volatile compounds during fermentation between the mutant and the pattern brewing yeast strains, the final acetaldehyde content from the mutant strain decreased to approximately one-third that of the pattern strain, which is an important advance to avoid or reduce acetaldehyde off-flavors in beer [7,11,53,73,75].…”
Section: Complementary Beer Volatile Compoundsmentioning
confidence: 99%
“…α-acetolactate is spontaneously decarboxylated to diacetyl outside the cell during the maturation step, when it is converted into acetoin (3-hydroxybutanone), which has no sensory characteristics (Figure 3). However, during low maturation temperatures, this conversion is very slow [31,32,33,73,74,75,76].…”
Section: Complementary Beer Volatile Compoundsmentioning
confidence: 99%
“…Another reason could be the synthesis of acetals, including acetaldehyde diethyl acetal. Acidic conditions promote the formation of acetals [34]. Kłosowski and Czupryński [35] observed an increase in the content of acetaldehyde diethyl acetal over successive hours during fermentation of distillery mashes.…”
Section: Resultsmentioning
confidence: 99%
“…Diacetyl content was determined by distillation according to the National Standard of the Peoples Republic of China (GB/T 4928-2008). Fusel alcohols, esters, and acetaldehyde were detected using headspace gas chromatography (GC-2010 PerkinElmer TurboMatrix 16, Shimadzu, China) with 3-heptanone as an internal standard [ 19 ].…”
Section: Methodsmentioning
confidence: 99%